2014
DOI: 10.1016/j.icarus.2014.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric thermal structure and cloud features in the southern hemisphere of Venus as retrieved from VIRTIS/VEX radiation measurements

Abstract: Thermal structure and cloud features in the atmosphere of Venus are investigated using spectroscopic nightside measurements recorded by the Visible and InfraRed Thermal Imaging Spectrometer (VIRTIS) aboard ESA's Venus Express mission in the moderate resolution infrared mapping channel (M-IR, 1-5 µm). New methodical approaches and retrieval results for the northern hemisphere have been recently described by Haus et al. (2013). Now, southern hemisphere maps of mesospheric temperature and cloud parameter fields a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
106
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(135 citation statements)
references
References 37 publications
20
106
2
Order By: Relevance
“…This global trend was derived by Ignatiev et al (2009) from VIRTIS-M spectroscopy and VMC images and was later confirmed by Lee et al (2012) by joint analysis of the VeRa and VIRTIS instruments on Venus Express. A recent detailed work based on VIRTIS data confirms this trend (Haus et al, 2014) which is also in agreement with earlier radiative transfer results (Zasova et al, 2007) and in situ measurements during the descent of the Venera and Pioneer Venus probes (Schubert, 1983) and from tracking of VEGA balloons (Preston et al, 1986).…”
Section: Cloud Altitudes and Vertical Wind Shearssupporting
confidence: 88%
See 2 more Smart Citations
“…This global trend was derived by Ignatiev et al (2009) from VIRTIS-M spectroscopy and VMC images and was later confirmed by Lee et al (2012) by joint analysis of the VeRa and VIRTIS instruments on Venus Express. A recent detailed work based on VIRTIS data confirms this trend (Haus et al, 2014) which is also in agreement with earlier radiative transfer results (Zasova et al, 2007) and in situ measurements during the descent of the Venera and Pioneer Venus probes (Schubert, 1983) and from tracking of VEGA balloons (Preston et al, 1986).…”
Section: Cloud Altitudes and Vertical Wind Shearssupporting
confidence: 88%
“…Several radiative transfer analysis place the cloud tops at altitudes of 67-71 km at the equator with a nearly constant altitude until 45-501S and a drop of altitude poleward of 501S reaching about 61-63 km over both poles (Ignatiev et al, 2009;Lee et al, 2012;Haus et al, 2014). Detailed studies of the cloud top motions can be traced back to measurements obtained by Mariner 10 in 1974 , Pioneer Venus in 1979-1985(Rossow et al, 1980Limaye and Suomi, 1981;Limaye et al, 1982Limaye et al, , 1988Limaye, 2007) and Galileo in 1990(Belton et al, 1991Toigo et al, 1994;Peralta et al, 2007;Kouyama et al, 2012).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The tropopause is located at around 60 km altitude at the base of the upper cloud layer (Tellmann et al, 2009). There is a clear trend for the cloud top altitude to decrease from equator toward the poles Ignatiev et al, 2009;Lee et al, 2012;Haus et al, 2014). The cloud top is defined as the level of the unity optical thickness at 4-5 μm, is located at 67 km in low latitude region and descends to 63 km at the poles (Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…We will derive pixel-by-pixel maps of CO absorption indices to study the hypothetical return flow of the Hadley cell (or indirect cell) (Schubert 1983), which may not be detected by cloud tracking results. Haus et al (2014) performed a comprehensive study of mesospheric temperature and cloud parameters while demonstrating usefulness of analyzing multi-window (1.74-, 2.3-, and 4.3-μm) spectra of the Venus night-side disk (VEX/VIRTIS-M). On Akatsuki, longwave infrared camera (LIR) can replace 4.3-μm observations by mapping the cloud-top temperatures at 8-12 μm (Fukuhara et al 2011), while IR2 provides 1.74-and 2.3-μm cloud opacity data.…”
Section: Co As a Tracer Of Atmospheric Circulationmentioning
confidence: 99%